2001
DOI: 10.1021/ja015808d
|View full text |Cite
|
Sign up to set email alerts
|

Plane-Wave Density Functional Theoretic Study of Formation of Clay-Polymer Nanocomposite Materials by Self-Catalyzed in Situ Intercalative Polymerization

Abstract: It has recently been shown that the intercalation and subsequent in situ polymerization of organic monomers within the interlayer of clay minerals yields nanocomposites with novel material properties. We present results of plane-wave density functional theory (DFT) based investigations into the initial stages of the polymerization of methanal and ethylenediamine within the interlayer of sodium montmorillonite. Nucleophilic attack of the amine on the aldehyde is only observed when the aldehyde is protonated or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 44 publications
(93 reference statements)
5
69
0
1
Order By: Relevance
“…On the other hand, some researchers have disclosed that for clay swelling to occur, water molecules must pass from external regions (i.e., external surfaces, internal surfaces, and micropores) to the interlayer gallery, passing between all clay edges. It has been determined that, in contrast to the chemically-inert basal plane, the edges of particles are extremely reactive [6][7][8][9], containing both Brönsted acid and base groups. Other authors [9][10][11] have reported that the reactive nature of clay layer edges has been implicated in catalysis reactions, such as polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some researchers have disclosed that for clay swelling to occur, water molecules must pass from external regions (i.e., external surfaces, internal surfaces, and micropores) to the interlayer gallery, passing between all clay edges. It has been determined that, in contrast to the chemically-inert basal plane, the edges of particles are extremely reactive [6][7][8][9], containing both Brönsted acid and base groups. Other authors [9][10][11] have reported that the reactive nature of clay layer edges has been implicated in catalysis reactions, such as polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…The other supports like MgO and Al 2 O 3 tend to decompose heteropolyacids [56][57][58][59]. Similar to heteropolyacids, montmorillonite clays also can be conveniently used as a solid acid catalyst in place of the conventional mineral acid reagents due to the presence of both Brønsted and Lewis acidities [60]. However, the applicability of montmorillonite clays for acid catalyzed organic transformations is restricted due to their low acidity.…”
Section: Introductionmentioning
confidence: 99%
“…These MMT-based catalysts combined the functions of the nanoparticles and MMT together, and exhibited synergetic effects [24][25][26]. Several methods have been adopted to prepare MMT-based composites, among which surfactant or polymerassisted methods are often applied [27][28][29][30]. For example, Pd-MMT nanocomposites were prepared with the aid of surfactants, which showed high selectivity for the partial hydrogenation of 1-phenyl-1-pentyne to 1-phenyl-cis-1-pentene [17].…”
Section: Introductionmentioning
confidence: 99%